(untitled) (Journal of Pathology of Nepal, 2016)
Urine cytology helps in the diagnosis of urothelial malignancies. There were no universally accepted reporting system despite several systems were suggested in the past. As a part of irst international effort to standardize urine cytology, The Paris System Working Group was formed comprising pathologists and urologists who met in 2013 at the International Congress of Cytology in Paris and proposed The Paris System (TPS). It was unanimously decided that the main aim of urine cytology was to detect high grade urothelial carcinoma. TPS consists of 7 diagnostic categories and also tries to deine several morphological criteria. TPS Atlas was published in 2016. This article tries to summarize and highlight essential points of The Paris System.